Pengaruh Total Quality Management dan Sistem Pengendalian Manajemen terhadap Kinerja Perusahaan pada Perusahaan Manufaktur di Indonesia sebagai Kajian Literatur - Nurhalizah, Intan; Nausta Pardede, Tiolina Evi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of Total Quality Management (TQM) and Management Control Systems (MCS) on firm performance, particularly in manufacturing companies in Indonesia. Firm performance is an important indicator in assessing operational effectiveness, productivity, and organizational competitiveness. TQM focuses on continuously improving product and process quality through the involvement of all members of the organization, while MCS plays a role in ensuring that all company activities are carried out in accordance with established strategic objectives and policies. This research employs a Systematic Literature Review (SLR) approach by analyzing scientific articles and both national and international journals published between 2015 to 2026. The results of the literature synthesis indicate that TQM and MCS have a positive and significant impact on firm performance, both individually and when integrated. Furthermore, the successful implementation of these two systems is strongly influenced by internal organizational factors, including organizational culture, management commitment, and employee participation. This study provides theoretical contributions to the development of management accounting literature and practical implications for management in designing strategies to improve firm performance.